2022
DOI: 10.3390/polym14245507
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Bottle Grade PET: Influence of HDPE Contamination on the Microstructure and Mechanical Performance of 3D Printed Parts

Abstract: As part of a project that aims to provide people with disabilities with simple assistive devices in Colombia, the possibility of creating a PET filament that can be printed by Fused Deposition Modelling (FDM) from beverage bottle waste was investigated, with the aim to remain as simple as possible in terms of plastic collection, sorting, processing, and printing. Recycled PET filaments were thus produced by extrusion from collected PET bottles, with the potential addition of HDPE, which comes from caps and rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The melting points of rHDPE and rPET are 131.7 and 249.9 C, respectively, which align with previous findings in the literature. 30,64,65 Melting and crystallization temperature of rPET increased, while that of rHDPE slightly decreased. The rHDPE appears to act as a nucleating agent for the rPET given the larger melting peak, which corresponds to a 3.5% increase in the degree of crystallization in the blend as well as the increase in crystallization temperature (Table 2).…”
Section: Thermal Analysis Dscmentioning
confidence: 98%
See 3 more Smart Citations
“…The melting points of rHDPE and rPET are 131.7 and 249.9 C, respectively, which align with previous findings in the literature. 30,64,65 Melting and crystallization temperature of rPET increased, while that of rHDPE slightly decreased. The rHDPE appears to act as a nucleating agent for the rPET given the larger melting peak, which corresponds to a 3.5% increase in the degree of crystallization in the blend as well as the increase in crystallization temperature (Table 2).…”
Section: Thermal Analysis Dscmentioning
confidence: 98%
“…7 Efforts are being made to identify sustainable feedstocks for 3D printing. 23,24 Several studies have expanded the range of recycled filament materials including PLA, 25,26 ABS, 27,28 PET, 29,30 HDPE, 9,27,31 and PC. 32 In fact, Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results demonstrated that recycled PET filaments could replace commercial filaments. Vaucher et al [ 128 ] evaluate the possibility to develop PET filaments form beverage bottle waste and the potential addition of HDPE from bottle caps and rings. Results showed that the HDPE presence does not affect the extrusion process or the 3D printing quality of the filaments.…”
Section: Sustainable Materials For 3d Printing: Giving Value To Wastementioning
confidence: 99%